Evaluation of COVID-19 patients requiring oxygen therapy in a tertiary care teaching hospital - Dave, Priti; Pore, Gargee M.; Singh, V. P.; Barsode, Supriya S. (International Journal of Advances in Medicine, 2021)
Background: COVID-19 disease is a public health emergency and declared as a pandemic in March 2020 by World Health Organization (WHO). Our aim was to study the clinical features, laboratory profile and outcome of COVID-19 patients needing oxygen therapy. Methods: All patients diagnosed to be having COVID-19 and SpO2 less than 94% on admission were included in the study. Detailed history, systemic examination and investigations were done and data was analyzed. Results: Out of 100 patients studied, 66% were males and 34% were females. Comorbidity was seen in 83% of cases, predominantly hypertension (30%) followed by diabetes mellitus (27%) and ischemic heart disease IHD (11%). Most common presenting complaints were breathlessness (84%) followed by dry cough (63%) and fever (48%). Mean values of absolute counts of neutrophils, lymphocytes, eosinophils and basophils were 4,835 cells/cu.mm, 1,332 cells/cumm, 66 cells/cumm and 86.5 cells/cumm respectively. Serum C-reactive protein (CRP) was raised in 90%, lactate dehydrogenase (LDH) in 96% and D-dimer in 64 % of cases on admission. Incidence of happy hypoxia was 16%. Mortality in our study was 2%. Greater the values of serum CRP, LDH, ferritin, lesser was the SpO2 of patients and greater the oxygen requirement. However no such correlation was found between D-Dimer and SpO2 of patients and their oxygen requirement. Conclusions: COVID-19 has varied presentations. The most common comorbidity was hypertension followed by diabetes mellitus. Serum inflammatory markers are raised in COVID disease. Eosinopenia can be a pointer towards COVID disease. One should be aware of the entity happy hypoxia seen in these patients.